2023
DOI: 10.3390/healthcare11182519
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Respiratory Telerehabilitation in Patients with Long COVID-19: A Systematic Review and Meta-Analysis

Andrés Calvache-Mateo,
Alejandro Heredia-Ciuró,
Javier Martín-Núñez
et al.

Abstract: The aim of this review was to identify, map, and synthesize the extent and nature of research activity on the use of telerehabilitation to support Long COVID-19 rehabilitation and examine the efficacy and safety of respiratory telerehabilitation in patients with Long COVID-19. A systematic review and meta-analysis of randomized controlled trials were performed. We included controlled trials that tested the effect of respiratory telerehabilitation interventions in patients with Long COVID-19 versus no intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Tele-rehabilitation, typically spanning 6–8 weeks with 3–4 weekly sessions lasting 20 to 60 minutes, offers a flexible and effective way to improve respiratory function and quality of life from patients’ homes via video conferencing. Supported by evidence of its efficacy and safety for COVID-19 patients, 168,169 this method reports high patient adherence due to its adaptability, without severe adverse events. 52,108 However, it faces challenges such as the need for individualized assessments, integration of technology into clinical practices, advanced practitioner training, and updates to legal and regulatory frameworks to ensure broad access and effective implementation, especially in disadvantaged areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tele-rehabilitation, typically spanning 6–8 weeks with 3–4 weekly sessions lasting 20 to 60 minutes, offers a flexible and effective way to improve respiratory function and quality of life from patients’ homes via video conferencing. Supported by evidence of its efficacy and safety for COVID-19 patients, 168,169 this method reports high patient adherence due to its adaptability, without severe adverse events. 52,108 However, it faces challenges such as the need for individualized assessments, integration of technology into clinical practices, advanced practitioner training, and updates to legal and regulatory frameworks to ensure broad access and effective implementation, especially in disadvantaged areas.…”
Section: Discussionmentioning
confidence: 99%
“…Breathing exercises have proven to significantly alleviate respiratory distress and improve lung function parameters (Vital Capacity, Total Lung Capacity, Forced Expiratory Volume in 1 s, Partial Pressure of Oxygen), as confirmed by systematic reviews. 166168 Moreover, improvements in respiratory function have been linked to increased strength in lower limb muscles and enhanced functional capacity, 169 emphasizing the role of comprehensive rehabilitation programs that incorporate breathing exercises to meet the specific needs of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The results of reviews indicated that digital physiotherapy intervention may be an effective strategy to improve quality of life and reduce dyspnoea, 56 functional capacity, 57 and has been found at least non-inferior to usual care. 58 However, caution should be exercised to avoid overestimating the results, 14 due to possible methodological shortcomings.…”
Section: Discussionmentioning
confidence: 99%
“…They will need timely assessment to consider escalation of COPD pharmacotherapy to relieve their dyspnea, which was shown to be worsened after COVID-19. Pulmonary rehabilitation should also be considered in these patients [16][17][18] . While patients with mild to moderate COVID-19 would have symptomatic deterioration, those with severe COVID-19 also had increase in future risks of severe exacerbation and mortality.…”
Section: Discussionmentioning
confidence: 99%